Analisis Perbandingan Dampak Serangan Black Hole pada Peformansi Protokol Routing OLSR dan AODV di Jaringan Wireless Mesh Network - Wian Virgi; Adhitya Bhawiyuga; Rakhmadhany Primananda (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Wireless Mesh network (WMN) is a set of wirelessly connected nodes forming a mesh topology. Over the WMN, the process of transmitting data information requires a path to get to the destination node, namely reactive protocol and proactive protocol. Security wise, routing protocols are still vulnerable to various forms of attack, especially against active attacks that can destroy, modify and deleting not only data but also the information within. Based on the said problems, the writer decided to make a research called Comparative Impact Analysis of Black Hole Attack on the Performance of OLSR and AODV routing Protocols in Wireless Mesh Network's Network. The results obtained in this study is that the black hole attack does affects the performance of AODV and OLSR routing protocols. The test was done using OMNET++ with three test scenarios, that is to say, without-attack; with multiple-attack nodes; and with big-probability of attack. Test parameters include throughput, end-to-end delay, packet loss and packet delivery ratio. The result of research using 18 nodes of attacker showed that packet loss on OLSR is higher than AODV which is proved by the highest packet loss result in AODV that only has 99.33% while OLSR has 99,50%.